Peranan Museum Indonesia sebagai Atraksi Wisata Melalui Pendekatan Total Nilai Ekonomi - Julita (Fakultas Pariwisata Universitas Pancasila, 2014)
This study aims to examine the role of Museum of Indonesia as tourists’ attraction by assessing its total economic value. The total economic value is measured by accumulating the use value and the non - use value based on the willingness to pay (WTP) of the visitors. In this study, the travel cost method was applied to assess the role of the Museum of Indonesia as a tourist attraction to assess the cost of travel, willingness to pay, motivation and perception of visitors. The results of this study indicate that the use value of the Museum of Indonesia using the travel cost method is Rp 4,627,210,056. While the value of the willingness to pay for the Museum of Indonesia is Rp 5,281,600,000 over the satisfaction of the Museum of Indonesia, and Rp 11,914,307,220, if tourists are prohibited from visiting the Museum of Indonesia. The total economic value of Museum of Indonesia is Rp 9,908,810,056 representing the accumulated use value and non-use value. The results suggest that the Museum of Indonesia has both existence value and bequest value as evidenced by the total economic value and from the high level of satisfaction felt by visitors to the Museum of Indonesia. Using a set of Likert-scale questions, perceptions and satisfactions have resulted in an average of 3,99 score for overall satisfactions. This research concludes that the Museum of Indonesia has a significant role as a tourist attraction considering the travel cost method figure, the willingness to pay, the total economic value, and the tourist perceptions in favoring the museum.